2015
DOI: 10.1016/j.chembiol.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Signaling by NOD-RIPK2 Is Inhibited by Clinically Relevant Type II Kinase Inhibitors

Abstract: SummaryRIPK2 mediates pro-inflammatory signaling from the bacterial sensors NOD1 and NOD2, and is an emerging therapeutic target in autoimmune and inflammatory diseases. We observed that cellular RIPK2 can be potently inhibited by type II inhibitors that displace the kinase activation segment, whereas ATP-competitive type I inhibition was only poorly effective. The most potent RIPK2 inhibitors were the US Food and Drug Administration-approved drugs ponatinib and regorafenib. Their mechanism of action was indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
126
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 54 publications
6
126
0
Order By: Relevance
“…However in chain A of the RIP2K K47R model the loop is structured and contains a short helix (Fig 3A). A similarly structured loop is observed in one monomer of the RIP2K D146N -STAU bound dimer and in recently described structures with bound inhibitors ponatinib, SB2 or biphenyl-sulfonamide (PDB codes: 4C8B, 5AR4, 5AR8 respectively) [38, 39]. These observations suggest that the Lys209 loop is in a dynamic equilibrium between a helical or disordered conformation.…”
Section: Discussionsupporting
confidence: 63%
“…However in chain A of the RIP2K K47R model the loop is structured and contains a short helix (Fig 3A). A similarly structured loop is observed in one monomer of the RIP2K D146N -STAU bound dimer and in recently described structures with bound inhibitors ponatinib, SB2 or biphenyl-sulfonamide (PDB codes: 4C8B, 5AR4, 5AR8 respectively) [38, 39]. These observations suggest that the Lys209 loop is in a dynamic equilibrium between a helical or disordered conformation.…”
Section: Discussionsupporting
confidence: 63%
“…RIPK2 is critically required for NOD1/2 signaling in response to intracellular bacterial exposure (35), and RIPK4 is required for proper development (9). Despite this, recent structural work has shown that a number of broad-spectrum kinase inhibitors target RIPK1, RIPK2 and RIPK3 with similar potency (1618). This same structural work has shown that while there are subtle structural differences that may help direct medicinal chemistry toward specific inhibitors; these three kinases overlap significantly in a 3D structural context, potentially make such efforts futile (18).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, recent structural work has shown that a number of broad-spectrum kinase inhibitors target RIPK1, RIPK2 and RIPK3 with similar potency (1618). This same structural work has shown that while there are subtle structural differences that may help direct medicinal chemistry toward specific inhibitors; these three kinases overlap significantly in a 3D structural context, potentially make such efforts futile (18). Additionally, work presented in this manuscript shows that they have overlapping molecular and biochemical activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If RIPK2 kinase activity is confirmed to be important, an FDA approved drug Ponatinib, which is shown to inhibit RIPK2 phosphorylation could provide an alternative to treat allergic asthma. 11 …”
mentioning
confidence: 99%